The Role of Political Stability and Foreign Direct Investment in Indonesia's Economic Growth - Kristofano, Yosef Yepta; Febriani, Ratu Eva (Asian Journal of Applied Business and Management, 2024)
This study aims to determine how the role of political stability and foreign direct investment to economic growth in indonesia. This study also aims to examine the influence of political stability and foreign direct investment (FDI) in playing an important role in economic growth in 34 provinces in Indonesia for the period 2018-2022. The method used in this study is a quantitative research method using secondary data in the form of panel data. The analysis tool used is panel regression. It was found that the positive relationship between political stability, Foreign Direct Investment (FDI), has a very important role for economic growth in Indonesia.